Paradigma tentang Tradisi dan Inovasi Pembelajaran di Lembaga Pendidikan Islam: Studi Kasus di Madrasah Tsanawiyah Negeri 1 Kota Bandung - Banyu Asih, Dianing; Safwandy Nugraha, Mulyawan (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This study aims to evaluate the paradigm of learning process in Madrasah Tsanawiyah Negeri 1 Bandung City in harmonizing Islamic learning traditions with technological innovations intended to improve the quality of education based on Islamic values. Using a qualitative approach and the CIPP (Context, Input, Process, Product) evaluation method, this study collected data through in-depth interviews with the principal as well as direct observation in the learning process. The results of this study show that traditional learning methods such as lectures, memorization and the use of textbooks are still quite relevant in shaping students' moral and spiritual character. Meanwhile, the existence of digital innovations such as E-Learning, gamification platforms, and blended learning has increased the motivation of student engagement in the learning process. However, the challenges of low digital literacy owned by educators and limited access to technology are the main obstacles in implementing digital innovations. This study concludes that the synergy between traditional learning methods and digital innovation is a strategic learning strategy in responding to the challenges of modernity without sacrificing Islamic values. This study recommends digital literacy training for educators, strengthening technological infrastructure and developing a curriculum that is adaptive to the times but still based on Islamic teachings and values. Further research is suggested to explore more specific learning models in the context of technology-based Islamic education to ensure effectiveness in various conditions and developments in the world of education.